Pemanfaatan Media Pembelajaran PAI Berbasis Digital dalam Melatih Kemampuan Berpikir Kritis Siswa di SMPS IT Al-Hijrah Laut Dendang - Muliyani, Tri; Arsyad, Junaidi; Muslem, Muslem (Cybernetics: Journal Educational Research and Social Studies, 2024)
This study aims to analyze the utilization of digital-based PAI learning media in training students' critical thinking skills at SMPS IT Al-Hijrah Laut Dendang. Digital learning media is a very important innovation in modern education, it can enable the delivery of more interesting material. This research uses descriptive qualitative method with data collection techniques through interviews, observation, and document analysis. The participants of the study included PAI teachers, students, and school staff. The results showed that the use of digital-based PAI learning media at SMS IT Al-Hijrah significantly improved students' critical thinking skills. The digital media used are visual such as books and audio visual such as movies or learning videos, computer-based media such as PPT and KHOT applications used in the PAI learning process. Students became more visible in the learning process showing improvement in the ability to identify problems, evaluate information, and make logical conclusions. It can be concluded that the research confirms that digital-based PAI learning media is effective in training students' critical thinking skills Thus, the results of this study are expected to contribute to improving the quality of PAI learning at SMPS IT Al-Hijrah Laut Dendang as well as being a reference for other schools in implementing digital technology in religious education.